2021
DOI: 10.1002/cam4.3846
|View full text |Cite
|
Sign up to set email alerts
|

MX2 mediates establishment of interferon response profile, regulates XAF1, and can sensitize melanoma cells to targeted therapy

Abstract: MX2 is an interferon inducible gene that is mostly known for its antiviral activity. We have previously demonstrated that MX2 is also associated with the tumorigenesis process in melanoma. However, it remains unknown which molecular mechanisms are regulated by MX2 in response to interferon signaling in this disease. Here, we report that MX2 is necessary for the establishment of an interferon‐induced transcriptional profile partially through regulation of STAT1 phosphorylation and other interferon‐related downs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…4C and Table S1†). Additionally, it was observed that the treatment caused an increase in the expression of anti-tumor genes, including Sox7 , 38 Xaf1 , 39 and B2m 40 (Fig. 4C and Table S1†).…”
Section: Resultsmentioning
confidence: 91%
“…4C and Table S1†). Additionally, it was observed that the treatment caused an increase in the expression of anti-tumor genes, including Sox7 , 38 Xaf1 , 39 and B2m 40 (Fig. 4C and Table S1†).…”
Section: Resultsmentioning
confidence: 91%
“…Liu and their colleagues demonstrated that the SLC2A3 could lead to the reduction of vitamin C uptake, therefore inhibiting leukemia development (Liu et al, 2020). Juraleviciute and their colleagues noticed that the MX2 could regulate the XAF1 and make the melanoma cells sensitive to targeted therapy (Juraleviciute et al, 2021). Wang and their colleagues found that the MX2 could suppress the glioblastoma progression through ERK/P38/NF-κB signaling (Wang et al, 2019b).…”
Section: Discussionmentioning
confidence: 99%
“…It can exert antiviral effects through IRF-3 and IRF-7 without involving IFN-γ signaling ( 48 ). In addition, MX2 may also modulate XAF1 to increase the sensitivity of melanoma cells to targeted therapies, which may be related to immune responses ( 49 ). Moreover, MX2 exerts immune effects by mediating multiple immune cells.…”
Section: Discussionmentioning
confidence: 99%